Transversal leukonychia and Beau lines in adult after hand-foot and mouth disease. - Milano, A. (European Journal of Pediatric Dermatology, 2014)
Case report. A 37-year-old woman without significant previous episodes in the personal history was first observed due to lesions of the hands, feet and forearms, arisen 4 days after the onset of hand-foot and mouth disease in the 3 year old daughter. The disease started with fever and burning lesions of the oral cavity; after two days appeared skin lesions. The physical examination highlighted papular, vesicular, exuding lesions of the palmar and plantar region, dorsal aspect of the feet and forearms; the lesions in the palmar and plantar region were fusiform (box in Fig. 1). These clinical features led to the diagnosis of hand-foot and mouth disease in an immunocompetent adult; a symptomatic therapy was prescribed. We reviewed the patient six weeks later due to the presence of nail lesions of the hands arisen from 2 weeks. The physical examination (Fig. 2) led us to diagnose transversal leukonychia and Beau lines of the nail caused by hand-foot and mouth disease.